Differential In Vitro Growth and Cell Killing of Cancer versus Benign Prostate Cells by Oncolytic Parainfluenza Virus - Kritika Kedarinath; Griffith D. Parks (Pathogens, 2022)
The development of effective oncolytic viruses will require understanding the differences in virus replication and killing between normal and cancer cells. Here, we have evaluated infections of metastatic cancer (22Rv1) and benign non-tumorigenic (BPH-1) prostate cell lines with a mutant parainfluenza virus 5 (P/V/F) encoding a defective V protein and a hyperfusogenic F protein. Under low multiplicity of infection (MOI), the P/V/F mutant efficiently spread in 22Rv1 cells but was restricted in BPH-1 cells due to type-I interferon (IFN-I) responses. In mixed co-cultures, the P/V/F mutant showed specificity towards and spread within the 22Rv1 cells versus BPH-1 cells. Under high MOI conditions, both BPH-1 and 22Rv1 cells showed efficient infection by the P/V/F mutant. However, compared to BPH-1 cells, the 22Rv1 cancer cells showed increased cytopathic effect, higher induction of caspase-8 and -9, and extensive syncytia formation. In 22Rv1 spheroid cultures, P/V/F infection was less efficient compared to monolayers, but the virus was able to spread through spheroids and induce death. These data indicate that IFN-I sensitivity is a major determinant of specificity of P/V/F spread through populations of cancer versus benign cells, and additionally, differences in activation of apoptotic pathways and syncytia formation can contribute to differential outcomes in cancer versus benign cells.